Profil Murid Berorientasi Literat Sains dan Problem Solver di Sekolah Dasar - Muslihah, Sri; Suryandari, Kartika Chrysti (Universitas Sebelas Maret, 2025)
Scientific literacy and problem solving are essential 21st-century competencies; however, results from PISA and TIMSS indicate that Indonesian students still perform poorly in these areas. This study aims to describe the profile of elementary school students oriented toward scientific literacy and problem solving, using a mixed methods approach conducted at a public elementary school in Kebumen District from April to June 2025. The participants consisted of fifth-grade students and their teacher. Data were collected through interviews, observations, and questionnaires using instruments validated by academic supervisors. The research procedure included planning, qualitative and quantitative data collection, and triangulation. Qualitative data were analyzed thematically, while quantitative data were analyzed descriptively using percentages and means. Results showed that 89% of students and 93% of teachers perceived students' scientific literacy and problem-solving abilities as still low, supported by qualitative findings indicating a lack of student independence in both aspects. Therefore, it is recommended that elementary schools develop integrated and contextual learning programs to enhance these competencies more effectively.Literasi sains dan problem solving merupakan kompetensi penting abad ke-21, namun hasil PISA dan TIMSS menunjukkan bahwa kemampuan murid Indonesia dalam kedua aspek ini masih rendah. Penelitian ini bertujuan mendeskripsikan profil murid sekolah dasar yang berorientasi pada literasi sains dan pemecahan masalah, dengan pendekatan kombinasi (mixed methods) di salah satu SD negeri di Kecamatan Kebumen pada April–Juni 2025. Peserta terdiri dari murid dan guru kelas V. Data dikumpulkan melalui wawancara, observasi, dan angket, menggunakan instrumen yang telah divalidasi oleh dosen pembimbing. Prosedur penelitian mencakup perencanaan, pengumpulan data kualitatif dan kuantitatif, serta triangulasi. Analisis data kualitatif dilakukan secara tematik, sedangkan data kuantitatif dianalisis deskriptif menggunakan persentase dan rerata. Hasil menunjukkan 89% murid dan 93% guru menilai kemampuan literasi sains dan problem solving masih rendah, yang diperkuat oleh temuan kualitatif mengenai kurangnya kemandirian murid dalam kedua aspek tersebut. Oleh karena itu, disarankan sekolah dasar mengembangkan pembelajaran yang terintegrasi dan kontekstual untuk meningkatkan kemampuan tersebut secara optimal.